+0  
 
0
130
1
avatar

What is (f+g)(x)?

 

f(x)=x3−x

g(x)=x3+2x2−10

 

(f+g)(x)= 

 


 

Guest Mar 30, 2018
 #1
avatar+7324 
+3

(f + g)(x)   =   f(x) + g(x)             Since  f(x)  =  x3 - x ,  we can replace  f(x)  with  x3 - x .

 

(f + g)(x)   =   (x3 - x) + g(x)        Since  g(x)  =  x3 + 2x2 - 10 ,  we can replace  g(x)  with  x3 + 2x2 - 10 .

 

(f + g)(x)   =   (x3 - x) + (x3 + 2x2 - 10)        We can drop the parenthesees.

 

(f + g)(x)   =   x3 - x + x3 + 2x2 - 10         Addition can be done in any order.

 

(f + g)(x)   =   x3 + x3 + 2x2 - x - 10         Combine like terms.

 

(f + g)(x)   =   2x3 + 2x2 - x - 10

hectictar  Mar 30, 2018

34 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.